2020
DOI: 10.1186/s12887-020-02247-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of dental age estimation with the Willems, Demirjian and Nolla methods in Spanish children: Comparative cross-sectional study

Abstract: Background: The objective of this study was to evaluate and compare the validity and accuracy of the Willems, Demirjian and Nolla methods in predicting chronological age in a Spanish ethnicity population. Methods: A sample of 604 orthopantomographs of Spanish children aged 4 to 13 years was evaluated by two independent evaluators. Descriptive statistics were applied to calculate the chronological age and dental age, presenting the mean and standard deviation. The difference between dental age and chronological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Internationally, using Demirjian method, an overestimation of dental age was found in Brazilians and Croats, 29 Malaysians, 30 Turks, 31 Bangladeshi and British, 32 Indians 2 and Spanish children. 27 The entire sample in this study showed an underestimation in dental age by -1.06 years using Nolla method which is similar with a Nepalese children study 14 and other population studies. 13,27,33,34 Whereas, Nolla's method has also shown overestimation in young children.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Internationally, using Demirjian method, an overestimation of dental age was found in Brazilians and Croats, 29 Malaysians, 30 Turks, 31 Bangladeshi and British, 32 Indians 2 and Spanish children. 27 The entire sample in this study showed an underestimation in dental age by -1.06 years using Nolla method which is similar with a Nepalese children study 14 and other population studies. 13,27,33,34 Whereas, Nolla's method has also shown overestimation in young children.…”
Section: Resultssupporting
confidence: 88%
“…27 The entire sample in this study showed an underestimation in dental age by -1.06 years using Nolla method which is similar with a Nepalese children study 14 and other population studies. 13,27,33,34 Whereas, Nolla's method has also shown overestimation in young children. 2,[35][36][37] Internationally, Nolla method has shown underestimation in the dental age when applied in Brazilians and Croats, 29 Malaysians, 30 Turks, 31 Bangladeshi and British, 32 Indians 38 and Spanish children.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Each of the teeth has an individual score assigned based on the Demirjian calcification stage. The scores of all the individual teeth are added up and converted to the chronological age based on sex [ 26 ].…”
Section: Tooth Growth and Developmentmentioning
confidence: 99%